Kontribusi Daya Ledak Otot Tungkai dan Koordinasi Mata Tangan Terhadap Ketepatan Smash Pemain Bola Voli Bukit Uncing - JONIKA TRISHANDRA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
ABSTRACK The problem with this research is that there are still many athletes who have poor jumping service accuracy such as not matching the desired target, proper accuracy in matches and training. So we need an innovation that can make the precision of the mesh. This study aims to determine the large contribution of explosive power to the accuracy of the smash in the athletes of the Bukit Uncing ball club, the greater the contribution of hand-eye coordination to the accuracy of the smash in the Bukit Uncing volleyball athletes, and the great power based on the explosive power of muscles and eye coordination. hands together on the accuracy of the smash on the athletes of the Uncing Hill volleyball club. This type of research is a correlation research that wants to see the relationship between the independent variable and the dependent variable. The population in this study were all athletes of the Bukit Uncing volleyball club who were actively participating in training. The sample in this study were all members of the uncing hill players. Based on the results of the analysis and discussion described in the previous section, in this chapter the following conclusions and suggestions can be drawn: (1) Explosive power is to increase the contribution to the performance of the Uncing Hill volleyball club, by 35.52%. (2) Eye-hand coordination contributes to the hill of accuracy of the uncing volleyball athletes' smash, by 20.79%. (3) The explosive power of the leg muscles (X1) and hand-eye coordination (X2) together contributed to the smash accuracy of the Bukit Uncing volleyball club athletes, by 40.70%. Keywords: Limb Muscle Explosiveness, Eye-Hand Coordination, Smash Accuracy And Volleyball